Clinical extension of proximal carious lesions compared to bitewing radiographs using photostimulable phosphor plates (PSP) - Khalaf, Mai E.; Baghdadi, Mariam T.; Faridoun, Afnan E.; Alshawaf, Nour M.; Qudeimat, Muawia A. (Journal of dentistry, 2022)
The aim of this study was to evaluate the use of digital bitewing radiographs using photostimulable phosphor (PSP) plates in the estimation of the true extension of proximal carious lesions. The sample size was calculated to be 70 teeth. Adult patients with a minimum of one posterior tooth with primary proximal caries lesions were included. A preoperative bitewing radiograph was taken and the extension of the carious lesion was measured from the most prominent point on the adjacent sound tooth to the deepest axial point of the lesion. An experienced general dentist provided the restorative treatment and made a polyvinyl siloxane impression of the cavity preparation. Clinical caries extension was measured from the most prominent point of the adjacent tooth until the deepest boundary of the axial wall of the preparation on the impression. Postoperative radiographs were taken at the completion of restorative care. The bitewing radiographs were done using PSP plates and caries extension measurements were performed using measuring tools of the digital radiography software. Pairwise comparisons were made between preoperative and postoperative radiographs, and the true clinical depth measurements using paired t-tests. In total, 73 teeth from 44 subjects were included. A significant difference of 0.82 mm was found between preoperative radiographs and clinical measurements (p<0.001). Similarly, comparisons between preoperative and postoperative radiographic measurements showed significant differences of 0.99 mm (p<0.001). The study found that the true clinical extension of proximal caries after non-selective caries removal was significantly deeper than the preoperative radiographic extension assessment. This was not influenced by the tooth type, the location of the tooth, or the affected tooth surfaces. When a non-selective caries removal strategy is adopted, clinicians should be aware that PSP bitewing radiographs underestimate the true clinical extension of proximal caries lesions. This will have an impact on clinicians’ practice and restorative treatment decisions.